Profile of Antituberculosis Therapy in Tuberculosis Patient with Diabetes Mellitus - Paramita, hilda ema; samirah (Brawijaya University, 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (M.tb.). People with weak immune conditions such as people with diabetes mellitus (DM) are more susceptible to TB infection. The aim of this research was to review the profile of antituberculosis therapy in pulmonary TB patients with DM. It was a descriptive observational study using retrospective data during period January 1, 2019, to January 31, 2020, which was conducted at Poli TB of Airlangga University Hospital. The samples used were medical records of adult patients over 18 years diagnosed with pulmonary tuberculosis and diabetes mellitus who received antituberculosis therapy and obtained as many as 32 medical records of patients. The results showed that the most widely used antituberculosis was Fixed- dose combination (FDC) asa many as 30 patients (93,8%) and 2 patients in special combination (6,4%). Special combination are given to patients with special conditions such as hypersensitivity to antituberculosis. The dose regimentation of antituberculosis given to the patient with controlled and uncontrolled diabetes during the intensive phase and continuation phase was 2 – 5 tablets of FDC. The patient’s diabetes control was measured by the value of glucose levels during treatment. Antidiabetic treatment given to pulmonary TB patients with DM was insulin in 20 patients (62,5%) and oral antidiabetic drugs (OAD) in 12 patients (37,5%). After obtaining the regimen therapy, most TB patients with controlled diabetes completed the treatment in 6 patients (26,1%) with duration of treatment of 6 months in 4 patients (17.4%) while patients with uncontrolled diabetes completed the treatment in 8 patients (34,8%) with duration of treatment more than 6 months in 9 patients (39,1%). Potential Drug- Related problems (DRP) identified in this research are 18 drug interactions (56,2%) and 14 suspected side effects (43,6%). Based on the results of research treatment and dosage regimens used in pulmonary TB patients with DM in Poli TB of Airlangga University Hospital have been following national TB guidelines